Backstepping Nonsingular Terminal Sliding Mode Control for PMSM With Finite-Time Disturbance Observer - Tong Li; Xudong Liu; Haisheng Yu (IEEE Access, 2021)
Aiming at the speed regulation problem of permanent magnet synchronous motor (PMSM) drives, a novel backstepping nonsingular terminal sliding mode control (BNTSMC) method with finite-time disturbance observer (FTDO) is proposed. In order to ensure excellent tracking and anti-disturbance performance, the backstepping nonsingular terminal sliding mode speed controller based on equivalent motor model and the recursive principle is designed for PMSM. The benefits of this approach are that the controller has asymptotic stability based on backstepping design and strong robustness for the matched disturbance based on sliding mode control. Then, to further improve the anti-disturbance performance, a finite-time disturbance observer is designed, and it is used to estimate the mismatched external disturbance in motor drive system. The stability of the system is also proved with Lyapunov criterion. Finally, the experimental results show that the proposed method has the advantages of fast convergence and strong robustness against parameter variations and external disturbance.